PERANCANGAN DAN PEMBUATAN XY-T RECODER BERBASIS DIGITAL = DESIGN AND MANUFACTURE XY-T RECORDER BASED ON DIGITAL - Muchamad Gozali; Yudi Irawadi (Jurnal Material Komponen dan Konstruksi, 2014)
An XY-T Recorder is a measuring equipment that function to record data of statical-testing result and it is shown in the form of graphs. The graphs of appearance indicate actual-condition of output censor such as Loadcell (Force),LVDT(deflection), Strain gauge (Strains) or Pressure. Design and manufacture of XY-T Recorder based in this digital is intended to satisfy the limit of XY-T Recorder analog available in B2TKS. The result of calibration shows certain calibration of 0.13% at the level trust of 95% with the factor k=2 and it indicates the accuracy to be fairly good.The result of experiment has displayed output of graphs with pattern and value magnitudes of relatively equal to the XY-TRecorder analogKeywords : XY-T Recorder digital, statical-testing, XY-T Recorder analog, CalibrationAbstrak XY-T Recorder adalah suatu alat ukur yang berfungsi untuk merekam data hasil uji statis yang ditampilkan dalam bentuk grafik. Grafik yang ditampilkan menunjukkan kondisi aktual dari besaran yang keluar dari sensor seperti loadcell (gaya), LVDT (defleksi), strain gauge (regangan) ataupun pressure (tekanan).Perancangan dan pembuatan XY-T Recorder berbasis digital ini bertujuan untuk memenuhi keterbatasan XY-T Recorder analog yang dimiliki oleh B2TKS. Dari hasil kalibrasi menunjukkan ketidakpastian kalibrasi 0,13% pada tingkat kepercayaan 95% dengan faktor k=2, hal ini menunjukkan ketelitian yang cukup bagus, dan dari hasil uji coba pada saat pengujian menunjukkan keluaran grafik dengan pola dan nilai besaran yang relatip sama dengan XY-T Recorder analog.Kata Kunci : XY-T Recorder digital, Uji Statis, XY-T Recorder analog,Kalibrasi